An integrated characterization of jujube (Ziziphus jujuba Mill.) grown in the North Adriatic Region - Miklavčič Višnjevec, Ana (Array, 2019)
Jujube (Ziziphus jujuba Mill.) has favourable horticultural properties including adaptation to arid conditions, abiotic and biotic stresses, as well as positive impact on human health. The present study describes the characterization of genetic diversity of the germplasm of jujube from the Istrian peninsula, the determination of important chemical compounds, antioxidative properties in relation to antibacterial and antifungal activities of jujube fruit extracts, and the determination of nutritional properties of jujube fruit. The results of the genetic analysis showed that most of the samples from the Istrian peninsula belong to two recently introduced varieties, 'Li' and 'Lang', and the most widespread local variety 'Navadna žižola'. The local variety has smaller fruit than the ‘Li’ and ‘Lang’ varieties, with thick and fleshy mesocarp. Chemical analysis indicated that fruits of the local variety contained a valuable source of dietary fibre ((9.7±0.6) g/100 g) and were rich in minerals such as (in g/100 g dry mass): potassium (829±51), calcium (177±11) and phosphorus (129±19). Aqueous extracts showed slight antibacterial activity, while ethanol extracts had higher mass fractions of phenolic compounds (expressed as gallic acid equivalents (GAE), 5.8-8.7 mg/g) than the aqueous extracts, but did not show antimicrobial activity. Compounds other than phenolic compounds in jujube fruit may be more biologically active. Based on the results of these analyses, the local Istrian jujube variety is a promising candidate for cultivation potential.